Stop and Search - Delsol, Rebekah. author. aut Link
XVII, 228 p.
Keywords: This book reviews the key controversies surrounding the police power to stop and search members of the public. It explores the history and development of these powers, assesses their effectiveness in tackling crime and their impact on public trust and confidence as well as on-going attempts at regulation and reform.